Trends and Progress in Corporate Dividend of Selected Steel Companies in India - Lalitha Mani, S.; Priya, S. (Indian Journal of Finance, 2010)
Dividend policy is an issue which can be examined only through intensive research works. During the last decades, a number of research works have been carried out on the subject both in India and aboard, attempting to explain and measure the different types of corporate dividend policy. The present study is an attempt in this direction. The study is based on a sample of five companies in steel industry covering a time period of thirteen years i.e from 1994-1995 to 2006-2007. It was found that stable dividend policy has been followed by the Bhushan steel and Kalyani steel whereas, the constant dividend policy has been followed by the TATA steel, Tayo Rolls and SAIL. It has also been said that the companies belonging to the Steel industry have declared dividends, which have varied significantly among the companies.